2005
DOI: 10.1254/jphs.scj05003x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Involved in the Contraction of Intrahepatic Portal Vein Branches by Clomipramine and Oxethazaine in Isolated Perfused Rat Livers

Abstract: Abstract. Clomipramine (CLM) and oxethazaine (OXZ) were previously reported to increase portal pressure by contracting portal vein branches (PVBs) in isolated perfused rat liver. In the present study, to characterize the contractile mechanisms, the effects of Y27632, HA1077, staurosporine, papaverine, SKF96365, and sulindac sulfide on the portal pressure increase induced by CLM and OXZ were examined comparatively with those induced by endothelin-1. The results suggest that 1) intrahepatic PVBs employ a Rho-kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…MTT test results were in accordance with the neutral red test, which is based on lysosome integrity (data not shown). Other researchers also reported similar results, but with different cell types, which confirms 3T3 as a suitable cell model (10 −7 to 10 −5 m range for PC12 prostate cancer cells and 28.9 μ m for HepAD38 liver cells). Complexation with HP‐β‐CD was found to decrease the in vitro toxicity of OXZ (IC 50 = 71 μ m ), probably because of the observed delayed release.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…MTT test results were in accordance with the neutral red test, which is based on lysosome integrity (data not shown). Other researchers also reported similar results, but with different cell types, which confirms 3T3 as a suitable cell model (10 −7 to 10 −5 m range for PC12 prostate cancer cells and 28.9 μ m for HepAD38 liver cells). Complexation with HP‐β‐CD was found to decrease the in vitro toxicity of OXZ (IC 50 = 71 μ m ), probably because of the observed delayed release.…”
Section: Discussionsupporting
confidence: 72%
“…OXZ also induces contraction of portal branched veins in perfused liver and in vitro haemolysis in the presence of Ca 2+ ions. Such effects are related to the anaesthetic action on calcium and sodium channels, which impairs nerve stimulus conduction . Interestingly, Zhang et al .…”
Section: Introductionmentioning
confidence: 99%
“…Kawada et al (29) reported that the ET-1-induced increase in portal pressure in IPRL was inhibited by Y27632. In our study (30), the portal pressure increases induced by CLM and OXZ were also inhibited by Y27632 and H1077, to a greater extent in the case of CLM (Fig. 4).…”
Section: +supporting
confidence: 66%
“…4); the portal pressure increase induced by ET-1 was also inhibited to a lesser extent, but the portal pressure increase by OXZ was somewhat enhanced (30). Sulindac sulfide is reported to inhibit proliferation of human colon cancer cells by inhibiting Ras signaling and by inhibiting storeoperated calcium entry and also to reduce amyloidogenic Aβ 42 secretion from special cells by inhibiting Rho activity, although it is still unknown whether any of these actions are related to the inhibition of the increase in perfusion pressure (30).…”
Section: +mentioning
confidence: 87%
“…The molecular mechanisms whereby CLP induces its antidepressant effects have not been well investigated. Some early reports indicate that CLP may affect serotonin uptake 35 , a Rho-kinase pathway and Ca(2+)-channels 36 . A more recent study using high throughput screening for inhibitors of the ubiquitin E3 ligase, Itch, indicates that CLP can specifically inhibit Itch ligase activity by binding irreversibly to HECT domains or catalytic cysteines 26 .…”
Section: Resultsmentioning
confidence: 99%